Philosophy of Science: Matter and Matter as an Ontology of Chemistry - Bayu Saputra; Suyitno Muslim; Novi Ayu Safira (Universitas Lampung, 2021)
Abstract: Philosophy of Science: Matter and Matter as an Ontology of Chemistry. Philosophy and science can be used by humans as an effort to understand the concepts and methods of a scientific discipline. Substantially and historically, philosophy and science have an important role in giving great influence to human life. One of the sciences, namely chemistry, is no exception, which has a major influence on human life. Ontology in chemistry can be understood as a science that discusses what we want to know and a study of chemical theory. A more in-depth ontology of chemistry is a discussion in order to find or get the essence of something related to chemistry. Chemistry is defined as the study of matter, its properties, structure, and changes in matter and the energy that accompanies these changes. This article aims to explain the ontology of chemistry, namely substances and matter according to experts and their development. This article uses qualitative research methods which include literature studies, where a review of books and journals is carried out to enrich and the results of empirical research are used as secondary data to strengthen arguments which are then synthesized into a single unit to provide meaningful information. The results showed that there are two ontological aspects of chemistry, namely the concept of chemistry which means the composition, nature, structure, change and energy that accompanies the change of a material and the object of chemistry, namely substance or matter.Keywords: Substance and Matter, Chemical Ontology DOI : 10.23960/jppk.v10.i3.2021.03